(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Leadership style is a series of systems that have important elements, namely influence, strong leadership ability to create cooperation so as to facilitate achieving the vision and mission of the organization. The research method used in this study is to use an observation approach. This leadership project method is divided into 2 namely; Empowering and Improvement and Community Service. Selected youths/girls are given training related to the concept of servant leadership and the big five personality theory. This collaboration aims to provide positive energy to the community, especially for children who are at the Al Hasanah Bone Bolango Orphanage through the presence of youth who are ready for change.